Optimasi Multiple Travelling Salesman Problem (M-TSP) Pada Penentuan Rute Optimal Penjemputan Penumpang Travel Menggunakan Algoritme Genetika. - Pande Made Rai Raditya; Candra Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Passengers enthusiasm in using travel services can be figured out through the increasing number of travel companies that are easily found in every city. Malang city is a region where the population is quite crowded with the large number of students, as well as students who come from outside the city. This makes more and more travel services emerge in Malang. Optimal route determination is a very notable problem to solve because it influences the time and operational costs of the vehicle. In this study, optimization of the optimal route determination using more than one salesman and starts from the travel office to the address of picking up each passenger. These problems belong to the problem of Multi Traveling Salesman Problem (M-TSP) and one of the algorithms to solve the M-TSP problem is by using genetic algorithm. In this case, it is used permutation representation, crossover reproduction process by one cut point crossover, mutation process by exchange mutation, and selection process by elitism selection. After conducting trials by using 30 locations, it is obtained that the results of the most optimal parameters is in the population which the population size is 80, with the number of cars traveling is 6, 450 generations, 0.6 and mr 0.4 and 0.4. The results of the program with these parameters resulted in the highest average fitness value of 8.09338.